Screening of novel SIRPα libraries using mammalian display - Kujala, Lotta (My University, 2025)
Binding proteins can be made from protein scaffolds composed protein domain structures that are not conventional antibodies or peptides. These scaffolds can be engineered by design for improved properties such as low immunogenicity and high stability. Signal inhibitory regulatory protein alpha (SIRPα) is of interest to Orion but here we are interested in probing this protein for possible engineering purposes. The aim of this study was to create four mutant libraries of SIRPα. One domain of the protein was engineered, and different sites were targeted for mutagenesis. Four amino acid mutations were done using NNK codons (N=any nucleotide, K=guanine or thymine) which encode all 20, naturally occurring, amino acids. The mutant libraries were constructed in bacteria and screened using mammalian display. The eukaryotic secretion machinery enabled the correct folding of the displayed proteins. Therefore, mammalian display could be used to screen for stable variants. The displayed libraries were then sorted using fluorescence-activated cell sorting (FACS) to distinguish between poor and improved variants. The variants were sequenced using next-generation sequencing (NGS) to identify the mutations present. The results suggest that SIRPα allows a wide variety of mutations in the targeted regions as all 20 amino acids were present. This makes SIRPα a promising scaffold for future engineering projects.
Keywords: FACS, library construction, mutagenesis, mammalian display, NGS, protein scaffold, protein engineering, SIRPα